2016
DOI: 10.1111/jmcb.12290
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy, Asset Prices, and Liquidity in Over-the-Counter Markets

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 64 publications
(83 reference statements)
1
101
1
Order By: Relevance
“…From Lemma 8 it follows that for u (q) = q 1 =(1 ), we need 2 (0; 1) and 2 to have an overlapping region supporting the type-II and the type-III equilibrium for all > 12 . 15 Otherwise, by Lemma 10, there exists a region which does not support trading in the secondary …nancial market for > 12 . For the matching technology in the secondary bond market, we follow related studies and choose M(n; 1 n) = n(1 n), which implies = n and p = 1 n. The following parameters need to be identi…ed: (i) preference parameters: ( ; A; ); (ii) the technology parameter: (n); (iii) bargaining power: ( ); (iv) and policy parameters (B; ).…”
Section: Numerical Examplementioning
confidence: 99%
“…From Lemma 8 it follows that for u (q) = q 1 =(1 ), we need 2 (0; 1) and 2 to have an overlapping region supporting the type-II and the type-III equilibrium for all > 12 . 15 Otherwise, by Lemma 10, there exists a region which does not support trading in the secondary …nancial market for > 12 . For the matching technology in the secondary bond market, we follow related studies and choose M(n; 1 n) = n(1 n), which implies = n and p = 1 n. The following parameters need to be identi…ed: (i) preference parameters: ( ; A; ); (ii) the technology parameter: (n); (iii) bargaining power: ( ); (iv) and policy parameters (B; ).…”
Section: Numerical Examplementioning
confidence: 99%
“…Research that is more closer related to the present paper is the study by Geromichalos and Herrenbrueck (2015), who also integrate an over-the-counter market in the spirit of Duffie et al (2005) into a New Monetarist framework. 7 The authors find that for secondary financial markets which do not exhibit any search frictions, i.e., where everybody is able to trade, bargaining achieves a superior outcome to that of centralized trading.…”
Section: Literaturementioning
confidence: 91%
“…In Geromichalos and Herrenbrueck (2012), we demonstrated that indirect asset liquidity can support many of the same conclusions, while offering an alternative microfoundation of imperfect asset substitutability: in this conception of liquidity, assets are substitutes to money because agents can sell them in a secondary financial market, and thus obtain the money needed to make a purchase. This detail is important because it implies that the structure of financial markets has first-order consequences for the 'moneyness' of different types of assets, and therefore their trading volumes and prices.…”
mentioning
confidence: 85%
“…The model described here is a simplified version of Geromichalos and Herrenbrueck (2012), and we limit the exposition to the essential details. As in the framework of Lagos and Wright (2005), time is discrete and goes on forever.…”
Section: The Modelmentioning
confidence: 99%